PEMERIKSAAN SAMPEL H5N1 PADA ITIK DENGAN TEKNIK REAL-TIME POLYMERASE CHAIN REACTION DI BALAI BESAR VETERINER WATES YOGYAKARTA - , AHMAD ABDUSSHOMAD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fieldwork practice or Praktek Kerja Lapangan (PKL) in Balai Besar Veteriner,Wates Yogyakarta was conducted to fulfill the practice fieldwork assignment which was scheduled by paramedic Veterinary study program. It was also conducted to gather data for final paper. This final paper was aimed to ascertain process inspecton sample of H5N1 on duck whith technique Real-Time Polymerase Chain Reaction ( PCR ) in balai besar veteriner wates yogyakarta. The substance collection was conducted in BBVet Wates Yogyakarta. The substance collected were about inspecton sample of H5N1 on duck whith technique Real-Time Polymerase Chain Reaction ( PCR ) in balai Balai Besar Veteriner Wates Yogyakarta. The inspecton result of the substance H5N1 sample on duck whith technique Real-Time Polymerase Chain Reaction ( PCR ) in the biotechnology lab Balai Besar Veteriner Wates Yogyakarta, from five sample it trial, undiscovered DNA from virus H5N1. The sample to emanate from BBVets employment area, namely Daerah Istimewa Yogyakarta Province, Jawa Tengah Province and Jawa Timur province.